Textbook citations increase subsequent citations in economics, except for the most cited articles - Bouwer, Danae (School of Economics, 2025)
This dissertation explores the intricate dynamics of information attribution and dissemination within academia, focusing on how textbook citation events influence subsequent citation patterns of academic literature. Rooted in the science of science, this study employs a comprehensive dataset of collaboration, affiliation, and citation metrics. The primary objective has been to uncover the nuanced mechanisms underlying the provenance of information by investigating how the attribution of ideas changes following a “notable event” – the citation of academic literature in well-known microeconomics textbooks. Defining two distinct effects associated with a “notable event” that could influence the subsequent citation counts of academic literature, this study examined the cessation effect, linked with decreasing citations, and the signalling effect, tied to increasing citations. Constructing a curated citation dataset of 610 observations and 18 variables, articles were categorised into treatment and control groups. The treatment group includes articles cited in microeconomics textbooks, while the control group, meticulously matched to ensure comparability, comprises uncited articles. A multiple linear regression model contrasts the citation trajectories of cited and uncited articles after the textbook citation event, simultaneously exploring the influence of various control variables on citation count. My findings shed light on the significant impact of textbook citation events on subsequent citation counts, ultimately enhancing the attribution of ideas. Notably, cited articles consistently achieve higher post-event citations, highlighting the reinforcement of attribution and confirming the presence of a signalling effect. However, for highly cited articles, a theoretical reduction in post-event citations was observed, suggesting a potential weakening of attribution and indicating the presence of a cessation effect. In addition to these central findings, the analysis of control variables revealed compelling insights. A positive correlation was identified between journal ranking, article length, and author citedness with citation counts, while a negative relationship surfaced between title length and citations. These secondary findings contributed to a deeper understanding of citation dynamics within academia. Drawing practical implications from these findings, this study affirms the robustness and enduring nature of academic referencing practices, elucidating that citing sources in textbooks significantly bolsters the preservation of information attribution. Furthermore, by drawing parallels between academic citation and data lineage, the research underscores the broader implications for data provenance, emphasising the importance of documenting data origins, sources, and methods thoroughly to ensure data reliability and traceability. Overall, this research offers a comprehensive analysis of the impact of textbook citation events on information attribution and dissemination within the field of economics. The study serves as a valuable contribution to the science of science, enriching the understanding of citation patterns and the complex social dynamics that shape the provenance of information in academia and beyond.